Mapping sub-volcanic geology using magnetic data. Issue 1 (1st December 2019) - Kivior, Irena; Markham, Stephen; Damte, Shiferaw
Summary: Volcanic layers within sedimentary basins cause significant problems for petroleum exploration because the attenuation of the seismic signal masks the underlying geology. A test study was conducted for the South Australia Government to map the thickness of volcanics and sub-volcanic geology over a large area in the Gawler Range Volcanics (GRV) province. The area is covered by good quality magnetic data. The thickness of volcanics and basement configuration was unknown as there has only been a limited amount of drilling. The Automatic Curve Matching (ACM) method was applied to located magnetic data and detected magnetic sources within different rock units, providing their depth, location, geometry and magnetic susceptibility. The magnetic susceptibilities detected by ACM allowed the differentiation of the volcanics and the underlying basement. The base of volcanics and the depth to the top of basement was mapped along 75km North-South profiles, that were spaced 1km apart over a distance of 220km. The volcanic and basement magnetic susceptibilities and the magnetic source distribution pattern, were used as key determinants to interpret the depth to the two interfaces. After the results for each interface were gridded, the surfaces were used to produce a 3D voxel model of the volcanics. A magnetic field was generated from the model and subtracted from the RTP data to produce the field generated by the sub-volcanic geology.